Impactful Research and Tooling for Program Correctness. - DARKE, PRIYANKA; METTA, RAVINDRA; MEDICHERLA, RAVEENDRA KUMAR; VENKATESH, R. (Communications of the ACM, 2022)
The article focuses on the development of the computer frameworks VeriAbs and VeriFuzz, which will help improve software quality. The authors discuss previous methods, such as bounded model checking (BMC), explain how VeriAbs will prove code correctness, and explain how VeriFuzz will automatically test for errors.